2010
DOI: 10.4028/www.scientific.net/amr.174.215
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Screen Ruling and Engraving Needle Tip Angle on Ink Transfer for Gravure

Abstract: Gravure printing is widely applied in packaging printing and the ink transfer is very important for printing quality. Ink transfer affects the ink uniform, thickness and dot gain, so it is necessary to optimize the parameter of the gravure plate making. At present, some investigations are developed for the ink transfer only qualitatively. In this paper, the influence of screen ruling and engraving needle tip angle on ink transfer is researched experimentally. Firstly, the standard test gravure plate was prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The ink transfer in rotogravure is greatly influenced by process parameters such as the nature of the substrate, screen ruling, ink viscosity, printing pressure, press speed, impression roller hardness, doctor blade angle, etc. [10][11][12] The lower viscosity ink undergoes higher spreading on the surface. Moreover, with the solvent loss from ink, the outermost layer of the ink tends to get sticky, which supports ink transfer onto the substrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ink transfer in rotogravure is greatly influenced by process parameters such as the nature of the substrate, screen ruling, ink viscosity, printing pressure, press speed, impression roller hardness, doctor blade angle, etc. [10][11][12] The lower viscosity ink undergoes higher spreading on the surface. Moreover, with the solvent loss from ink, the outermost layer of the ink tends to get sticky, which supports ink transfer onto the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…14 Moreover, for a liquid of given viscosity, a decrease in surface tension and contact angle between ink and substrate leads to greater pick-out and higher spreading, whereas higher surface tension results in fewer pinholes with better spreading. [13][14][15] Deng et al 12 and Gencoglu 15 showed that higher screen ruling and the engraving needle tip angle and lower cell depth lead to an increase in the ink density and reduction in dot gain, while ink transfer is higher at finer screen rulings. Maximum dot gain is obtained on polyester substrates because of their smoother surface characteristics.…”
Section: Introductionmentioning
confidence: 99%